Production and transformation of residential space of low income population in Bogota under neoliberal policies (1990-2010) (Ciudades, 2017)
Summary of the PhD “Producción y transformación del espacio residencial de la población de bajos ingresos en Bogotá en el marco de las políticas neoliberales, 1990 – 2008. Una interpretación a partir de cuatro casos de estudio en la localidad de Ciudad Bolívar” by Carlos Alberto Torres Tovar on the University Institute of Urban Research of the University of Valladolid on July 5th, 2011. Directors: María A. Castrillo Romón, from the University of Valladolid, and Beatriz García Moreno, of the National University of Colombia. Board: Dr. Professor Alfonso Álvarez Mora, Dr. Professor Juan Luis de las Rivas Sanz, Dr. Professor Carlos González Lobo, Dr. Professor Agustín Hernández Aja, Dr. Professor José Fariña Tojo.
Keywords: abstract; doctoral thesis